A Subspace Embedding Method in L2 Norm via Fast Cauchy Transform. (11th December 2013) - Xiang, Xu; Cheng, Li-Zhi
Abstract : We propose a subspace embedding method via Fast Cauchy Transform (FCT) in L 2 norm. It is motivated by and complements the work of the subspace embedding method in L p norm, for all p ∈ [ 1, ∞ ] except p = 2, by K. L. Clarkson (ACM-SIAM, 2013). Unlike the traditionally used orthogonal basis in Johnson-Lindenstrauss (JL) embedding, we employ the well-conditioned basis in L 2 norm to obtain concentration property of FCT in L 2 norm.